Is There a Role of Using a Rapid Finger Prick Antibody Test in Screening for Celiac Disease in Children? - Kristina Baraba Dekanić; Ivona Butorac Ahel; Lucija Ružman; Jasmina Dolinšek; Jernej Dolinšek; Goran Palčevski (Gastroenterology Research and Practice)
Introduction. Celiac disease (CD) is an autoimmune disease triggered by gluten in genetically predisposed individuals. Despite the increasing prevalence of CD, many patients remain undiagnosed. Standard serology tests are expensive and invasive, so several point-of-care tests (POC) for CD have been developed. We aimed to determine the prevalence of CD in first-grade pupils in Primorje-Gorski Kotar County, Croatia, using a POC test. Methods. A Biocard celiac test that detects IgA antibodies to tissue transglutaminase in whole blood was used to screen for celiac disease in healthy first-grade children born in 2011 and 2012 who consumed gluten without restrictions. Results. 1478 children were tested, and none of them were tested positive with a rapid test. In 10 children (0,6%), IgA deficiency has been suspected; only 4 of them agreed to be tested further for total IgA, anti-tTG, and anti-DGP antibodies. IgA deficiency was confirmed in 3 patients, and in all 4 children, CD has been excluded. Conclusion. Our results have not confirmed the usefulness of the POC test in screening the general population of first-grade schoolchildren. Further research is needed to establish the true epidemiology of CD in Primorje-Gorski Kotar County and to confirm the value of the rapid test in comparison with standard antibody CD testing.